PARADIGMATIC ANALYSIS ON SIGNS USED ON SPESIAL SAMBAL (SS) AND RUMAH CABE RESTAURANTS’NAME BOARDS - KOESPUTANTRI, RIZDA RAGIEL MARLIANE (Jurnal Ilmiah Mahasiswa FIB, 2013)
A restaurant’s name board can be used as a sign to inform people brief information about the restaurant, such as the restaurant’s name or the menus. The design of a restaurant’s name board should make people interested in visiting the restaurant. In this study, semiotic approach is employed to know the signs used on the restaurant’s name board, such as, symbol, index, and icon. This approach is also used to find out the differences in meaning carried by the objects of the study. The objects of the study are Spesial Sambal (SS) and Rumah Cabe restaurants’ name boards. Those restaurants are chosen as the object of this study because both of them are the most favorite restaurants in Malang. This study aims to identify (1) the signs found on Spesial Sambal (SS) and Rumah Cabe restaurants’ name boards and (2) the differences in meaning carried by Spesial Sambal (SS) and Rumah Cabe restaurants’ name boards based on paradigmatic analysis theory.      This study is qualitative in the form of document analysis. The data are the signs used on Spesial Sambal (SS) and Rumah Cabe restaurants’ name boards. In selecting the data, the writer chooses restaurants that serve spicy food which get highest rates from people on the internet. In analyzing the data, the writer uses some theories, such as from Smith, Peirce, and Saussure.            The results of this study show that each restaurant name board contains semiotic signs which are symbol, index, and icon. The differences in meaning carried by the restaurants’ name boards are based on the signs used on each name board. According to the paradigmatic analysis on each signifier used on the restaurants’ name boards, it can be seen that the original signs are possible to change with other alternative signs which have similar characteristics. However, it might change the messages which are delivered to the customers.            Some suggestions are made for the next writers to conduct similar study by choosing other sources as the objects, such as advertisements, video or movie to obtain various results. The next writers can also use other theories in order to enrich the results of the study.Keywords: Semiotics, Sign, Symbol, Index, Icon, Paradigmatic Analysis, Spesial Sambal (SS), Rumah Cabe